A politician and his books: the Venizelos library in Chania - Llewellyn-Smith, Michael (The Historical Review/La Revue Historique, 2018)
Eleftherios Venizelos loved books. He collected them, read them, and annotated them. With few exceptions, the most important being his translation of Thucydides into modern Greek, he did not write them. Books were an important part of his life, and he continued until the end to buy them. His collection of books is of historical and psychological interest. After his death in 1936, the books were transferred from his apartment in Paris and his wife’s house in Athens to the Venizelos family house in Halepa, near Chania in Crete. After many vicissitudes, especially during the German occupation of Crete, they came to rest in Chania Municipal Library, where they remain today. This paper explores Venizelos’ reading habits and preferences through this collection, showing that he used books both for professional information, for pleasure, and to improve his knowledge of foreign languages, in particular English. He was familiar with the great authors from Homer to Shakespeare; with philosophy from Aristotle to Bergson; with poetry, fiction, but especially with political thought, history and literature. It is good that the collection remains in the hands in the Municipal Library in the city where Venizelos lived and worked.